1985
DOI: 10.1159/000146089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pilocarpine Treatment and of Electrical Stimulation of the Vagus Nerve on the Rat Parathyroid Gland, with Special Reference to the Alteration of Storage Granules

Abstract: Effects of pilocarpine treatment and of electrical vagal stimulation on the rat parathyroid were studied ultrastructurally. The number of type I storage granules with a narrow halo (NSG-I) and hat of type II storage granules having a wide halo (NSG-II) were calculated. After pilocarpine treatment, NSG-I gradually decreased and reached a minimum at 30 min; in contrast, NSG-II gradually increased and reached a maximum at 20 min, but thereafter it slightly decreased and instead vacuolar bodies increased. Excludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Acid phosphatase reaction performed in both control and experimental animals exhibited almost the same results as those observed in the PT gland of rats under short-term high calcium levels (Setoguti et al, 1985a). Therefore, on the basis of our present results, we suggest that SGs are normally transformed from type I into type I1 as a result of hydrolysis, and that hydrolysis of SGs is accelerated by parasympathetic stimulation without changes of SCL (Setoguti et al, 1985b). Fig.…”
Section: Effect Of Parasympathetic Stimulation Onsupporting
confidence: 62%
“…Acid phosphatase reaction performed in both control and experimental animals exhibited almost the same results as those observed in the PT gland of rats under short-term high calcium levels (Setoguti et al, 1985a). Therefore, on the basis of our present results, we suggest that SGs are normally transformed from type I into type I1 as a result of hydrolysis, and that hydrolysis of SGs is accelerated by parasympathetic stimulation without changes of SCL (Setoguti et al, 1985b). Fig.…”
Section: Effect Of Parasympathetic Stimulation Onsupporting
confidence: 62%
“…Some species exhibit diurnal PTH secretory rhythms that may be controlled by these nerves (Fischer ^ al., 1982). Setoguti et^ al. (1985b) have shown that vagal stimulation (parasympathetic) leads to increased conversion of Type I secretory granules to Type II secretory granules.…”
Section: Pth Secretionmentioning
confidence: 99%